Isolated Lateral Chronic Exertional Compartment Syndrome of the Leg: A New Entity?. Issue 12 (24th December 2019) - van Zantvoort, Antonia P.M.; Hundscheid, Henricus P.H.; de Bruijn, Johan A.; Hoogeveen, Adwin R.; Teijink, Joep A.W.; Scheltinga, Marc R.M.
Background: Chronic exertional compartment syndrome (CECS) mostly occurs in the anterior or deep posterior compartments (ant-CECS and dp-CECS, respectively) of the leg. It is generally accepted that CECS of the third or lateral compartment (lat-CECS) always occurs together with ant-CECS. However, whether exertional leg pain (ELP) can be caused by an isolated form of lat-CECS is unknown. Purpose: To determine the existence of isolated lat-CECS and study whether history taking and a physical examination aid in discriminating between different subtypes of CECS. Study Design: Case series; Level of evidence, 4. Methods: Patients were eligible for this single-center study, conducted between January 2013 and February 2018, if they reported anterolateral ELP and completed a questionnaire scoring the frequency and intensity of pain, tightness, cramps, muscle weakness, and paresthesia during rest and exercise. They were asked to mark areas of altered foot skin sensation, if present, on a drawing. All patients underwent a dynamic intracompartmental pressure (ICP) measurement of the anterior and lateral compartments simultaneously. The diagnosis of CECS was confirmed by elevated ICP (Pedowitz criteria). There were 3 patient groups: (1) isolated ant-CECS with elevated ICP in the anterior compartment and normal ICP in the lateral compartment, (2) isolated lat-CECS with elevated ICP in the lateral compartment but normal ICP in the anterior compartment, and (3) ant-/lat-CECS with elevated ICP in both the anterior and lateral compartments. Results: A total of 73 patients with anterolateral ELP fulfilled study criteria (isolated ant-CECS: n = 26; isolated lat-CECS: n = 5; ant-/lat-CECS: n = 42). Group differences were not observed regarding age (isolated ant-CECS: median, 26 years [range, 13-68 years]; isolated lat-CECS: median, 20 years [range, 17-63 years]; ant-/lat-CECS: median, 28 years [range, 17-57 years]; χ 2 (2) = 0.466; P = .79), sex (isolated ant-CECS: 50% male; isolated lat-CECS: 40% male; ant-/lat-CECS: 62% male; P = .49), or bilateral symptoms (isolated ant-CECS: 54%; isolated lat-CECS: 80%; ant-/lat-CECS: 69%; P = .40). However, cramps at rest were present in a portion of the patients with isolated ant-CECS (38%) and ant-/lat-CECS (57%) but not in those with isolated lat-CECS ( P = .032). Patient drawings of altered foot skin sensation did not contribute to the diagnosis ( P = .92). ICP values after provocation were all lower in patients with isolated ant-CECS and isolated lat-CECS compared with those with ant-/lat-CECS ( P < .05). Conclusion: Seven percent of patients with CECS and anterolateral ELP who had symptoms due to isolated lat-CECS in the presence of normal muscle pressure in the anterior compartment.